Detection of Salmonella typhi Using Multiplex and Monoplex PCR in Tifoid Fever Patients - Andika Aliviameita; Meryn Linanda Agustin; Anggie Wedha Puspita; Miftahul Mushlih; Puspitasari Puspitasari; Yanik Purwanti; Arief Wisaksono (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2019)
Typhoid fever is a disease caused by Salmonella typhi infection. This disease is still a global problem. The purpose of this study was to develop a rapid detection method for Salmonella using molecular methods utilizing Inv A and Fim-C Genes. Two methods compared, which are Multiplex and monoplex PCR. The sample is in the form of the patient's blood, which is stored at 3 ml EDTA vacutainer tube consisting of 10 positive samples and five negative samples. The criteria for samples used previously have tested by widal/ immunoserology (titer more than 1/160). The results showed that multiplex PCR for detection of Salmonella using the Inv A gene and fim c gene not recommended because too many bands produced. The application of monoplex in the Inv A gene gives better results than the Fim C gene. In conclusion, the monoplex application on Inv A gene recommended than Fim C gene used to detect S. typhi in human blood samples.